![\begin{gathered} \text{Given} \\ F(x)=8+11x-3x^2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cv2mbs03l53ivs8srjf4jzm0yksgp2rucm.png)
a. Solve for F(5).
To solve for F(5), substitute x = 5 to the given function, and evaluate accordingly to the operation
![\begin{gathered} F(x)=8+11x-3x^2 \\ F(5)=8+11(5)-3(5)^2 \\ F(5)=8+55-3(25) \\ F(5)=63-75 \\ F(5)=-12 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vs8dfi0xyu14s35x9twvb80exur741ezaz.png)
b. Solve for F(x+b)
Again we substitute the paremeters by x+b to the given function, and we get
![\begin{gathered} F(x)=8+11x-3x^2 \\ F(x+b)=8+11(x+b)-3(x+b)^2 \\ F(x+b)=8+11x+11b-3(x^2+2xb+b^2) \\ F(x+b)=8+11x+11b-3x^2-6xb-3b^2 \\ \\ \text{Since we cannot simplify further, we just rearrange} \\ \text{the final answer according to the degree of the terms} \\ F(x+b)=-3x^2-3b^2-6xb+11x+11b+8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/w0e17daw8ept54d1m5vcvim69kqjw672gt.png)
c. Solve for F(-3)
Substitute x = -3
![\begin{gathered} F(x)=8+11x-3x^2 \\ F(-3)=8+11(-3)-3(-3)^2 \\ F(-3)=8-33-3(9) \\ F(-3)=-25-27 \\ F(-3)=-52 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/vr3j3xgcxm0pa69gzff954fyeavtzo0qzk.png)